Antibacterial properties of tualang honey and its effect in burn wound management: a comparative study - Nasir Nur-Azida; Halim Ahmad; Singh Kirnpal-Kaur; Dorai Ananda; Haneef Mehru-Nisha (BMC, 2010)
Abstract Background The use of honey as a natural product of Apis spp. for burn treatment has been widely applied for centuries. Tualang honey has been reported to have antibacterial properties against various microorganisms, including those from burn-related diagnoses, and is cheaper and easier to be absorbed by Aquacel dressing. The aim of this study is to evaluate the potential antibacterial properties of tualang honey dressing and to determine its effectiveness as a partial thickness burn wound dressing. Methods In order to quantitate the bioburden of the swabs, pour plates were performed to obtain the colony count (CFU/ml). Swabs obtained from burn wounds were streaked on blood agar and MacConkey agar for bacterial isolation and identification. Later, antibacterial activity of Aquacel-tualang honey, Aquacel-Manuka honey, Aquacel-Ag and Aquacel- plain dressings against bacteria isolated from patients were tested (in-vitro) to see the effectiveness of those dressings by zone of inhibition assays. Results Seven organisms were isolated. Four types of Gram-negative bacteria, namely Enterobacter cloacae, Klebsiella pneumoniae, Pseudomonas spp. and Acinetobacter spp., and three Gram-positive bacteria, namely Staphylococcus aureus, coagulase-negative Staphylococcus aureus (CONS) and Streptococcus spp., were isolated. Total bacterial count decreased on day 6 and onwards. In the in-vitro antibacterial study, Aquacel-Ag and Aquacel-Manuka honey dressings gave better zone of inhibition for Gram positive bacteria compared to Aquacel-Tualang honey dressing. However, comparable results were obtained against Gram negative bacteria tested with Aquacel-Manuka honey and Aquacel-Tualang honey dressing. Conclusions Tualang honey has a bactericidal as well as bacteriostatic effect. It is useful as a dressing, as it is easier to apply and is less sticky compared to Manuka honey. However, for Gram positive bacteria, tualang honey is not as effective as usual care products such as silver-based dressing or medical grade honey dressing.